PERKEMBANGAN KURIKULUM MERDEKA DI INDONESIA - Ramadhani, Jeliza; Yusadi, Ardini; Sriwahyuni, Eci (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
The aim of this research is to identify and obtain information about the development of the independent curriculum in Indonesia. The method used in this research is Systematic Literature Review (SLR). SLR is a planned review to answer specific research questions using a systematic and explicit methodology to identify, select, and critically evaluate research results included in the literature review. This research explains the development of the independent curriculum in Indonesia. The results of this research show that to implement the independent learning curriculum, of course various parties, especially teachers, will be faced with various kinds of challenges. For example, the readiness of teachers as implementers of the concepts built in to the curriculum. Various pessimistic attitudes reveal teachers' unpreparedness for implementing the independent curriculum. In the independent curriculum, the structure of the independent curriculum is intra curricular, the implementation of the Pancasila profile project. The independent curriculum is one of the solutions needed to help direct students towards a progressive mindset and can provide color in society.